Opportunities for Orphan Crops: Expected Economic Benefits From Biotechnology - Zambrano, Patricia; Wood-Sichra, Ulrike; Ruhinduka, Remidius D.; Phillip, Dayo; Nin Pratt, Alejandro; Komen, John; Kikulwe, Enoch Mutebi; Falck Zepeda, José; Dzanku, Fred M.; Chambers, Judith A. (Frontiers in Plant Science, 2022)
An enabling, evidence-based decision-making framework is critical to support agricultural biotechnology innovation, and to ensure farmers’ access to genetically modified (GM) crops, including orphan crop varieties. A key element, and often a challenge in the decision-making process, involves the balancing of identified potential risks with expected economic benefits from GM crops. The latter is particularly challenging in the case of orphan crops, for which solid economic data is scarce. To address this challenge, the International Food Policy Research Institute (IFPRI) in collaboration with local economists analyzed the expected economic benefits to farmers and consumers from the adoption of GM crops in 5 sub-Saharan African countries. This paper focuses on case studies involving insect-resistant cowpea in Nigeria and Ghana; disease-resistant cassava in Uganda and Tanzania; and disease-resistant banana in Uganda. Estimations from these case studies show substantial economic benefits to farmers and consumers from the timely adoption and planting in farmers’ fields of GM orphan crops. Our analysis also shows how the benefits would significantly be reduced by regulatory or other delays that affect the timely release of these crops. These findings underscore the importance of having an enabling policy environment and regulatory system—covering, among other elements, biosafety and food/feed safety assessment, and varietal release registration—that is efficient, predictable, and transparent to ensure that the projected economic benefits are delivered and realized in a timely manner.